(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Major consideration affecting all aspects of tourism planning including fundamental decisions on attitude and policy is dependent on the extent to which either development or community support is to be given precedence. This paper attempts to assess the factors that can enhance or hinder community support for tourism development, a kind of symbiotic relationship in the harnessing tourism potentials. After all, tourism exerts both detrimental and beneficial influences on local community. It degrades irreversibly the very attractions which justifies and attract it, and on the other hand it enhances the socio-economic interest of the local people and authorities are challenged to appreciate the value of community support in tourism development. 316 semi structured interview were conducted on six different ethnic communities with varying ethno cultural tourism potentials. The result reveal that most resident communities are ready to support ethno-cultural tourism development in their community if they are going to benefit (economically), through job creation, infrastructural development and cultural revitalization. The paper recommends that planning and development of tourism should be geared towards ethno-cultural tourism as strongly advocated by local community to gain their support for a sustainable tourism development initiative